(untitled) (American Journal of Technology and Applied Sciences, 2024)
The study presents a comprehensive scientific and economic analysis of the use of heat pumps for high-quality heating of apartments, with a focus on global trends and the specific context of Uzbekistan. Heat pumps, recognized for their energy efficiency and environmental benefits, have gained widespread adoption in various regions around the world. This paper examines the economic feasibility, energy savings, and environmental impact of heat pump technology, comparing it to conventional heating systems. The analysis includes a review of global best practices, case studies, and the current state of heat pump adoption in Uzbekistan. The findings highlight the potential for significant energy savings and reduced greenhouse gas emissions through the widespread adoption of heat pumps in Uzbekistan. However, challenges such as high initial costs, lack of awareness, and the need for supportive policies are identified as barriers to broader implementation. The study concludes with recommendations for enhancing the adoption of heat pumps in Uzbekistan, emphasizing the role of government incentives, public awareness campaigns, and international cooperation.